Respons Aktivitas Biologi Tanah terhadap Berbagai Formulasi Pupuk Organik Berdasarkan Populasi Mikroba dan Respirasi CO2: Soil Biological Activity Response to Various Organic Fertilizer Formulations Based on Microbial Population and CO2 Respiration - Restu Wulansari; Davina Raisha Nathania (Pusat Penelitian Teh dan Kina, 2026)
Soil biological activity is an important indicator in assessing the effectiveness of organic fertilizers on increasing soil fertility. This study aims to evaluate the response of soil biological activity based on microbial populations and CO₂ respiration rates in various organic fertilizer formulations. The study was conducted at the Research Institute for Tea and Chinchona, Bandung, using a Completely Randomized Design (CRD) with seven organic fertilizer treatments, namely tea waste biocompost, tea waste biocompost + Trichoderma spp., Bioneensis, Bioorganomineral, vermicompost, goat manure, and chicken manure, each with three replications. The parameters observed included the number of soil microbial populations and CO₂ respiration rates. The results showed that the type of organic fertilizer significantly affected the microbial population and soil CO₂ respiration. The highest microbial population was found in the tea waste biocompost, goat manure, and chicken manure treatments. The highest CO₂ respiration rate was found in the goat manure and tea waste biocompost + Trichoderma spp. treatments. The high CO₂ respiration was in line with the increased soil microbial activity, indicating the important role of organic fertilizer in increasing soil biological activity. Based on these results, tea waste biocompost + Trichoderma spp. and goat manure are recommended for field application because they are able to increase microbial activity and soil respiration optimally. Keywords: CO₂ respiration, microbial population, organic fertilizers, tea waste biocompost, soil biological